Synthesis and Studies of PANI/Cerium dioxide Nanocomposites - P. Selvarajan2*, E. Kumar1,3, (Journal of Experimental Sciences, 2010)
Nanomaterials possess unique and interesting mechanical, optical, electrical, magnetic, thermal and other properties. These materials range from inorganic to organic, crystalline to amorphous, which can be found as single particles, aggregates, powders, nanowires, quantum dots, nanofilms, nanofibres, nanotubes. Nanocomposites are also possessing unique properties like pure nanomaterials. In this work, We report the synthesis of nanocomposite of polymer added cerium dioxide (CeO2) by microwave-assisted solution method and it was fabricated via in situ polymerization of the monomer in the presence of cerium dioxide (ceria) nanoparticles. The as-synthesized ceria nanoparticles and PANI/ceria nanocomposite materials were subjected to various studies like XRD, SEM, FT-IR, TEMÂ Â  and UV-Visible Spectroscopic studies.